Respuesta :

Answer:

a) 3

b) -4

c) -1/3

d) -2

e) -4/3

Step-by-step explanation:

a) 6w=2  ,   w=6/2    , ie. w= 3

b) 6+w=2   ,w=2-6   , ie. w= -4

c) 6w+2= 0,  6w=  0-2 , 6w= -2 , w= -2/6, ie. w= -1/3

d) 6w+2= -10, 6w= -10-2,  6w= -12, w= -12/6 , ie. w= -2

e) 6w+2= 12w+10, 6w-12w = 10-2 ( here we interchanged the digits to get the variables or you can say the terms having variables in this case 'w' to the same side. hereby changing the sign from '+' to '-')

so

6w-12w = 10-2 ,-6w=8, w= -8/6, ie. w= -4/3

You can check your answers by substituting with the answers in place of the variable and check if the equation is solved.

Tell me if this was helpful

In an equation whenever we transpose the sign changes and multiplication changes to division addition to subtraction minus changes toplus and we should put all the like terms in one side all the variables in one side and all the coefficients in one side


HOPE IT HELPS!!!!!!!!!!!!
MARK ME THE BRAINLIEST!!!!!!!!!!!!!!
Ver imagen syeda1727

Otras preguntas